Study on the gestational age-related histogenesis of human fetal suprarenal glands - Annamraju, Maruti Ram; Boddeti, Ravindra Kumar; Velichety, Subhadra Devi; Battalapalli, Srihari Rao (Asian Journal of Medical Sciences, 2020)
Background: Fetal suprarenal gland consists of three zones. They are the outer definitive zone or neocortex (DZ) that forms adult Zona Glomerulosa (ZG), the centrally located fetal zone and a third transitional zone (TZ) the future adult Zona Fasciculata (ZF) which lies just between the neocortex and fetal zone (FZ). The inner ZF that consists of large eosinophilic cells, and the outer definitive zone (DZ) consists of small, densely packed basophilic cells. As early as in 6th week of gestational Age, pheochromoblasts derived from the neural crest migrate through the fetal cortex to form the medulla at a later stage of development. The medulla unrecognizable as a distinct structure in the suprarenal gland throughout most of the gestation, except for small clusters or nests of chromaffin cells scattered throughout the body of the cortex. Aims and Objective: The study was designed and aimed to understand the early developmental histology of suprarenal gland. Materials and Methods: Study conducted at the Department of Anatomy, SV Medical College, Tirupati, Andhra Pradesh, India. The study was carried out by processing representative samples of fetal suprarenal tissues of 13 weeks, 17 weeks, 24 weeks, 25 weeks and 38 weeks gestational age. While processing, we observed the standard dissection procedure and histopathological tissue processing for the human samples. Results: Peripheral narrower and darker definitive zone or true cortex and an inner wider and lighter fetal zone was observed at 13, 17, 24 weeks with 10x objective. The demarcation between cortex and medulla could be seen clearly at 24 weeks. At 25 weeks capsule is very thick and vascular. A well-differentiated gland tissue with clear demarcation of cortex and medulla and a large central vein was observed. At 38 weeks degeneration of fetal zone with a thick-walled central vein was observed at lower magnification (10x objective) Conclusion: Observations on prenatal microscopic structure and gestational age-related changes in suprarenal glands form the basis for understanding structural changes and a foetal database for the local population.